The Efficiency of Local Tax Collection in Technical Implementation Unit of West Nusa Tenggara Provincial Revenue Management Board - Baihaki, Muhammad; Basuki, Prayitno; Chaidir, Taufiq (Universitas Negeri Malang, 2019)
The study aimed to investigate the efficiency level of regional tax collection in nine technical implementation units in Regional Revenue Management Board of NTB. Data was analyzed by means of Data Envelopment Analysis (DEA). This study applied quantitative study which utilized descriptive analysis. Data was collected by using a direct interview to the principals and any related stakeholders and by observating and documentating schemes. The findings of the study suggested that eight UPTBs suffers from inefficiency determined by lack of capabilty of each UPTBs to target the predetermined regional tax revenue based on their potential and incapability to achieve its predetermined target. In addition, it was also determined by excessive human resources in each UPTBs and the placement of human resources who did not have relevant or adequate required capabilityKeywords: Technical Efficiency; Technical Implementation; Regional Revenue Management Board; DEAJEL Codes: G28; H21